1999
DOI: 10.1046/j.1365-2567.1999.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of graft‐versus‐host disease, I. A locus on Chromosome 1 influences development of acute graft‐versus‐host disease in a major histocompatibility complex mismatched murine model

Abstract: Graft-versus-host disease (GVHD) is the major complication occurring after bone marrow transplantation. The severity of GVHD varies widely, with this variation generally being attributed to variation in the degree of disparity between host and donor for minor histocompatibility antigens. However, it is also possible that other forms of polymorphism, such as polymorphisms in immune effector molecules, might play a significant role in determining GVHD severity. In order to investigate this hypothesis, we are stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…5). The implicated interval on chromosome 1 contains several candidate genes such as Adprt1, which plays a key role in immune reactions, and Tlr5, which is a member of a group of Toll-like receptors involved in the activation of the immune system in response to various pathogens that has been frequently implicated in murine autoimmunity (27,(33)(34)(35)(36)(37)(38). This locus corresponds to a region on human chromosome 1, ϳ30 Mb apart from the D1S498 marker and ϳ60 Mb from the D1S252 marker, that demonstrated linkage ( p ϳ 0.01 and p ϳ 0.0001, respectively) with infection levels by S. mansoni in humans (39).…”
Section: Discussionmentioning
confidence: 99%
“…5). The implicated interval on chromosome 1 contains several candidate genes such as Adprt1, which plays a key role in immune reactions, and Tlr5, which is a member of a group of Toll-like receptors involved in the activation of the immune system in response to various pathogens that has been frequently implicated in murine autoimmunity (27,(33)(34)(35)(36)(37)(38). This locus corresponds to a region on human chromosome 1, ϳ30 Mb apart from the D1S498 marker and ϳ60 Mb from the D1S252 marker, that demonstrated linkage ( p ϳ 0.01 and p ϳ 0.0001, respectively) with infection levels by S. mansoni in humans (39).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our studies have indicated that loci on chromosomes 1 and 2, in the vicinity of the Mtv7 and IL-1 loci respectively, influence GVHD development in the B6D2F1 model. [33][34][35] The differential outcome of GVHD in the B6D2F1 model is thought to be due to differential activation of Figure 1 The B6D2F1 parent→F1 murine GVHD model. In this model, transfer of parental strain C57BL/6 lymphoid cells into (C57BL/6 × DBA/2)F1 (ie, B6D2F1) recipients results in acute GVHD whereas transfer of parental strain DBA/2 lymphoid cells into B6D2F1 recipients results in chronic GVHD.…”
Section: Quantity Vs Quality Of T Cell Activationmentioning
confidence: 99%
“…In that model, we were able to show that the severity of GVHD in a completely MHCmismatched setting depended on the genotype of donor mice at two specific non-MHC loci-one on chromosome 1 and one on chromosome 2. 33,34 Mice with a specific genotype at these loci had a significantly lowered risk of inducing severe acute GVHD, even though they were MHC-mismatched with recipients. 34 This indicates that it is possible to choose donors whose non-MHC genetics will reduce the risk of their cells inducing life-threatening GVHD in recipients, even when there is not a perfect MHC match.…”
Section: Too Many Restrictions On Choosing a Donor?mentioning
confidence: 99%
“…23,24 Analysis of the mean maximum percent weight losses in B6D2F1 recipients of B10.D2 BX cells revealed significantly different maximum percent weight losses between recipients of cells from B10.D2 BX mice that were homozygous at the marker D1Mit57 and recipients of cells from B10.D2 BX donors that were heterozygous at D1Mit57 a n = number of donor mice with the genotype given. b Mean ± standard deviation.…”
Section: Linkage Analysismentioning
confidence: 99%
“…[19][20][21][22] We previously identified a locus on chromosome 1 that exerts a major influence on the development of acute GVHD in this model. 23,24 Candidate genes on chromosome 1 include the gene encoding the superantigen Mtv7 and the gene encoding the cell surface molecule CD48. Mtv7 is an endogenous superantigen that can influence negative selection of T cells.…”
mentioning
confidence: 99%